2022
DOI: 10.1200/jco.22.00380
|View full text |Cite
|
Sign up to set email alerts
|

FLOT Versus FLOT/Trastuzumab/Pertuzumab Perioperative Therapy of Human Epidermal Growth Factor Receptor 2–Positive Resectable Esophagogastric Adenocarcinoma: A Randomized Phase II Trial of the AIO EGA Study Group

Abstract: PURPOSE High pathologic complete response (pCR) rates and comparably good survival data were seen in a phase II trial combining perioperative fluorouracil, leucovorin, oxaliplatin, and docetaxel (FLOT) chemotherapy with trastuzumab for resectable, esophagogastric adenocarcinoma (EGA). The current trial evaluates the addition of trastuzumab and pertuzumab to FLOT as perioperative treatment for human epidermal growth factor receptor 2–positive resectable EGA. METHODS In this multicenter, randomized phase II/III … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 30 publications
(44 reference statements)
3
29
0
1
Order By: Relevance
“…The HER-FLOT regimen was also found to be safe, with a promising pCR rate of >20% achieving pathological complete response (pCR) [ 70 , 71 ]. Furthermore, the German phase II study PETRARCA showed recently that the addition of trastuzumab and pertuzumab to perioperative FLOT is feasible and significantly improved pCR compared to FLOT only [ 72 ].…”
Section: Systemic Therapy In Oligometastatic Esophagogastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The HER-FLOT regimen was also found to be safe, with a promising pCR rate of >20% achieving pathological complete response (pCR) [ 70 , 71 ]. Furthermore, the German phase II study PETRARCA showed recently that the addition of trastuzumab and pertuzumab to perioperative FLOT is feasible and significantly improved pCR compared to FLOT only [ 72 ].…”
Section: Systemic Therapy In Oligometastatic Esophagogastric Cancermentioning
confidence: 99%
“…Thus, the shown high response rates of fluoropyrimidine plus platinum-based chemotherapy plus docetaxel and/or PD-1 or HER-2-directed therapy [ 25 , 26 , 49 , 70 , 72 ] make the combinations attractive especially in the limited metastatic disease to enable a possible surgical R0 resection.…”
Section: Systemic Therapy In Oligometastatic Esophagogastric Cancermentioning
confidence: 99%
“…Pathological complete response was seen in 21.5% (n = 12/56) of patients with locally advanced HER2-positive gastric cancers following neoadjuvant combination therapy, exceeding the pre-specified threshold of 20% to warrant further investigation [ 95 ]. Dual HER2-inhibition using trastuzumab and pertuzumab with FLOT chemotherapy in the randomised PETRARCA study (n = 81) has also been shown to significantly improve pathological complete response (35% vs. 12%, p = 0.02) and nodal response (68% vs. 39%) over FLOT alone [ 96 ]. However, this was at the expense of higher rates of grade ≥3 diarrhoea (41% vs. 5%) and leukopenia (23% vs. 13%) with combination treatment when compared to FLOT chemotherapy.…”
Section: Her2 Targeting In the Curative Paradigmmentioning
confidence: 99%
“…Of note, a randomized phase II study in Her 2 positive, resectable esophagogastric adenocarcinoma showed that a combination of two Her-2 targeted antibodies, trastuzumab and pertuzumab to the FLOT chemotherapy backbone improved pCR from 12% to 35%. 52 Unlike when combined with chemotherapy, addition of Her-2 targeted therapy does not appear to benefit patients undergoing chemoradiation. The randomized phase III RTOG 1010 study evaluated the efficacy of trastuzumab in Her-2 overexpressing, resectable, esophageal cancer patients undergoing chemoradiation.…”
Section: Unique Subpopulations In Geacmentioning
confidence: 99%